2012
DOI: 10.1002/jsfa.5748
|View full text |Cite
|
Sign up to set email alerts
|

Identification of physicochemical properties of Scylla paramamosain allergen, arginin kinase

Abstract: AK is an important food allergen despite its unstable physicochemical properties of digestibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
5
10
0
Order By: Relevance
“…This investigation showed that the high molecular weight band corresponding to haemocyanin in the raw extract was not observed in the cooked extract. Arginine kinase was also not identified within the cooked mud crab extract, consistent with being heat labile as documented previously for other crab species [30, 31]. However, there was also evidence for heat stable proteins such as tropomyosin, with mud crab tropomyosin retaining IgE reactivity as a monomer, aggregate and fragment in the cooked extract.…”
Section: Discussionsupporting
confidence: 82%
“…This investigation showed that the high molecular weight band corresponding to haemocyanin in the raw extract was not observed in the cooked extract. Arginine kinase was also not identified within the cooked mud crab extract, consistent with being heat labile as documented previously for other crab species [30, 31]. However, there was also evidence for heat stable proteins such as tropomyosin, with mud crab tropomyosin retaining IgE reactivity as a monomer, aggregate and fragment in the cooked extract.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, arginine kinase is a globular protein, which tends to unfold during heating, exposing hydrophobic amino acids, which are normally inside the protein. The exposed hydrophobic amino acids from different molecules will interact in such a way, that formation of larger protein aggregates will occur [25]. Cross-linking of arginine kinase may also be caused by polyphenol oxidase-mediated cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to tropomyosin, arginine kinase is highly abundant in invertebrate muscle, and hitherto, it has also been described in various other shellfish species as well as other invertebrates such as mites, cockroaches, crickets, silk worms, and the Indian meal moth . Unlike tropomyosins, they display unstable physicochemical properties and do not resist thermal and acid‐base treatment .…”
Section: Allergensmentioning
confidence: 99%